Plasmacytoid dendritic cell expansion defines a distinct subset of RUNX1-mutated acute myeloid leukemia - Xiao, Wenbin (Blood, 2021)
Plasmacytoid dendritic cells (pDCs) are the principal natural type I interferon–producing dendritic cells. Neoplastic expansion of pDCs and pDC precursors leads to blastic plasmacytoid dendritic cell neoplasm (BPDCN), and clonal expansion of mature pDCs has been described in chronic myelomonocytic leukemia. The role of pDC expansion in acute myeloid leukemia (AML) is poorly studied. Here, we characterize patients with AML with pDC expansion (pDC-AML), which we observe in ∼5% of AML cases. pDC-AMLs often possess cross-lineage antigen expression and have adverse risk stratification with poor outcome. RUNX1 mutations are the most common somatic alterations in pDC-AML (>70%) and are much more common than in AML without pDC expansion and BPDCN. We demonstrate that pDCs are clonally related to, as well as originate from, leukemic blasts in pDC-AML. We further demonstrate that leukemic blasts from RUNX1-mutated AML upregulate a pDC transcriptional program, poising the cells toward pDC differentiation and expansion. Finally, tagraxofusp, a targeted therapy directed to CD123, reduces leukemic burden and eliminates pDCs in a patient-derived xenograft model. In conclusion, pDC-AML is characterized by a high frequency of RUNX1 mutations and increased expression of a pDC transcriptional program. CD123 targeting represents a potential treatment approach for pDC-AML.